2019
DOI: 10.1007/s11136-019-02127-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in changes of HRQoL over a 1-year period after radiotherapy in Norwegian breast cancer patients: results of cluster analyses

Abstract: Purpose The diversity in long-term changes in health-related quality of life (HRQoL) among breast cancer (BC) survivors is poorly understood. The aim of this study was to identify clusters of trajectories (subgroups of patients with similar patterns of changes) of selected HRQoL domains over a 1-year period after radiotherapy (RT) in BC patients. Methods The group consisted of 250 BC patients referred for postoperative RT. Global quality of life (QoL), functions, and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Thus, anxious patients at baseline can be suggested programs based on art therapy to prevent this deterioration. The results support a recent study in patients with breast cancer that also found three clusters of trajectories for the five HRQoL dimensions after treatment 33 . Over a period of 1 year, they identified three subgroups of patients for the global functioning variable.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, anxious patients at baseline can be suggested programs based on art therapy to prevent this deterioration. The results support a recent study in patients with breast cancer that also found three clusters of trajectories for the five HRQoL dimensions after treatment 33 . Over a period of 1 year, they identified three subgroups of patients for the global functioning variable.…”
Section: Discussionsupporting
confidence: 89%
“…Although we chose a two‐trajectory model for GHS, this choice was motivated only by the small number of patients in the third trajectory ( n = 2); our first analyses had led us to the same conclusion, identifying three patient profiles. Lazarewicz et al 33 reported that a majority of patients belonged to the “high” (44%) or “medium” (43%) GHS group. This supports our finding that 55% of our sample belonged to the “improvement” trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could therefore be appropriate to move beyond investigating mean scores and identify how symptoms and late effects may develop and change over time in subgroups of patients and survivors. A recent study measuring responses to the QLQ-C30 in 250 BC patients over a 1-year period after completion of radiotherapy thus found three distinct types of clusters of trajectories for all outcome variables, i.e., stable trajectories of high, medium, and low HRQoL [45], suggesting that identifying the predictors of the trajectories could identify those with special rehabilitation needs.…”
Section: Discussionmentioning
confidence: 96%
“…This issue is particularly relevant to breast cancer (BC) patients who, in most developed countries, receive proper healthcare and constitute the largest group of cancer survivors [8]. Thus, tertiary prevention encompassing restoration and maintenance of good QoL after treatment becomes the key priority [9][10][11][12][13]. This positive trend was confirmed in longitudinal studies estimating QoL on the basis of average-level data [9][10][11][13][14][15] or in subgroups defined by treatment modalities [16,17].…”
Section: Introductionmentioning
confidence: 94%